Multi-omic analyses reveal the waterlogging induced responses in Magnolia sinostellata - Fang, Xiaoai; Fan, Lu; Zhou, Huijuan; Yan, Huiling; Ding, Fangbing; Li, Renna; Linghu, Yuwei; Xie, Bin; Wang, Yaling (Frontiers in Plant Science, 2025)
Waterlogging stress poses a significant constraint on the cultivation and landscape utilization of Magnolia species. Currently, the molecular mechanisms underlying their adaptation remain largely unexplored. Magnolia sinostellata, a riparian species with exceptional waterlogging tolerance, provides an ideal model to decipher these mechanisms. Here, we integrated transcriptomic and metabolomic analyses to investigate the dynamic responses of different tissues (roots, stems, leaves) in M. sinostellata to waterlogging stress at 0 h, 6 h, and 72 h. Roots showed the strongest response, with 12,538 DEGs and 178 DEMs. Additionally, the morphological adaptations included hypertrophic lenticel, aerenchyma formation and adventitious root development. The combined analysis of transcriptome and metabolome indicates that the plant signal transduction pathway plays an important role in responding to waterlogging stress. Our findings demonstrate that multiple phytohormone signaling pathways, including IAA, JA, CTK, GA, and ET, collectively regulate the tolerance of M. Sinostellata to waterlogging stress. Notably, we identified jasmonic acid (JA) as a negative regulator of this adaptive response, contrasting with its positive role in other species, and pinpointed key candidate genes (CKX and JAR1). Taken together, this study advances our theoretical understanding of woody plant adaptation to waterlogging stress and delivers practical genetic tools for developing waterlogging-resistant ornamental cultivars.